Mackey functors for posets - Carrión Santiago, Guille; Díaz-Ramos, Antonio (Springer Nature, 2025)
We define Mackey functors over posets mimicking the classical notion and introduce a weak version of them. Then we show that they are acyclic by analyzing cofibrant and pseudoprojective objects in the category of functors indexed in a filtered poset. As application, we study homotopy colimits over posets and we give a homology decomposition for the classifying space of the Bianchi group
Keywords: Algebras topológicas; Higher limit; Model category; Pseudo-projective; Mackey functor; Acyclic functor; Homology decomposition; Bianchi group